2019
DOI: 10.3389/fgene.2019.00492
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis Reveals Extensive Genetic Variations of WRKYs in Solanaceae and Functional Variations of CaWRKYs in Pepper

Abstract: As a conserved protein family, WRKY has been shown to be involved in multiple biological processes in plants. However, the mechanism of functional diversity for WRKYs in pepper has not been well elucidated. Here, a total of 223 WRKY members from solanaceae crops including pepper, tomato and potato, were analyzed using comparative genomics. A tremendous genetic variation among WRKY members of different solanaceous plants or groups was demonstrated by the comparison of some WRKY features, including number/size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…S1). Findings in PhWRKYs were in accordance with previous works describing the WRKY family in different species of the Solanaceae family, including potato, pepper, eggplant, and tomato (Huang et al 2012;Yang et al 2015;Cheng et al 2016;Zhang et al 2017;Cheng et al 2019) and species of other families like Arabidopsis, carrot, rice, and Brachypodium distachyon (Wu et al 2005;Rushton et al 2010;Tripathi et al 2012;Li et al 2016). Moreover, almost all senescence-associated PhWRKYs showed the most conserved WRKYGQK heptapeptide sequence, and only one member of the subgroup IIc showed a variation in this sequence (PhWRKY051).…”
Section: Multiple Sequence-alignments and Phylogenetic Classi Cation Of Wrky Proteins In P Hybridasupporting
confidence: 89%
See 2 more Smart Citations
“…S1). Findings in PhWRKYs were in accordance with previous works describing the WRKY family in different species of the Solanaceae family, including potato, pepper, eggplant, and tomato (Huang et al 2012;Yang et al 2015;Cheng et al 2016;Zhang et al 2017;Cheng et al 2019) and species of other families like Arabidopsis, carrot, rice, and Brachypodium distachyon (Wu et al 2005;Rushton et al 2010;Tripathi et al 2012;Li et al 2016). Moreover, almost all senescence-associated PhWRKYs showed the most conserved WRKYGQK heptapeptide sequence, and only one member of the subgroup IIc showed a variation in this sequence (PhWRKY051).…”
Section: Multiple Sequence-alignments and Phylogenetic Classi Cation Of Wrky Proteins In P Hybridasupporting
confidence: 89%
“…This fact could explain the reduction in the number of WRKYs identi ed in petunia when compared to Arabidopsis. In accordance, a total of 81 members were identi ed in tomato and potato, while a signi cantly lower number (65) was identi ed in pepper (Cheng et al 2019). Moreover, the total number of WRKY members in the parental species of P. hybrida has not been assessed yet (Bombarely et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group II WRKYs can be divided into five subGroups (IIa-IIe) 10 . It is well recognized that Group I WRKY members are the evolutionary ancestors of the other WRKYs and that they exist only in lower plants 11,12 . The complexity of this gene family involves different molecular levels, from the transcriptional self-regulation through microRNAs to post-transcriptional events, such as alternative splicing, post-translational regulation through ubiquitin proteasome system and MAPK cascade 9 .…”
mentioning
confidence: 99%
“…Despite this, to date no studies have examined WRKY gene family components and their different characteristics in wild potato species. A few data on this gene family are available only in the cultivated potato, where Zhang et al 21 , Liu et al 22 and Cheng et al 12 identified 79, 82 and 81 StWRKYs, respectively. Previously, Dellagi et al 23 identified StWRKY1 as a good candidate for functional studies, and Shahzad et al 24 overexpressed it in potato.…”
mentioning
confidence: 99%